Multi-omics analysis of the potential association between metabolic features of hypothyroidism in the first half of pregnancy and Th17/Treg balance - Wang, Yixin; Xu, Yajuan; Li, Jingjing; Zhang, Miao; Sun, Zongzong; Zhang, Chenchen; Lin, Pengkun (Frontiers in Immunology, 2026)
The aim of this study is to conduct a multi-omics investigation of the metabolic profile of hypothyroidism in the first half of pregnancy and its correlation with the Th17/Treg balance.30 pregnant women with hypothyroidism (hypothyroidism group) and 30 healthy pregnant women (control group) in the first half of pregnancy were included. Results showed that sphingosine (Sph) and BH3 interacting domain death agonist (BID) were significantly upregulated in hypothyroidism group. Sphingolipid signaling pathway was the significantly enriched pathway. Sph and BID in cord blood of hypothyroidism group were also higher. An increase was shown in the Th17/Treg ratio and Th17 cells, and a decrease shown in Treg cells in the hypothyroidism group. The incidence of gestational diabetes mellitus in the hypothyroidism group was significantly higher. Sph and BID were positively correlated with Th17/Treg ratio. Sph levels were positively correlated with Th17 percentage and gestational diabetes.In conclusion, using a multi-omics approach, we identified distinct metabolic alterations in women with hypothyroidism in the first half of pregnancy, characterized by elevated levels of sphingosine and BID and a disrupted Th17/Treg balance. These changes may contribute to the pathogenesis of early gestational hypothyroidism, offering new theoretical insights into its underlying mechanisms.